Students' Perceptions of Online Learning Using YouTube During the Covid-19 Pandemic - Nining Fitriani; Andreas Heri Kurniawan (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2022)
The purpose of this study was to determine the perception of students majoring in computer accounting, Junior year, STEKOM University Semarang on online learning using YouTube. The method used in this research was mixed method. The location of the research was conducted in the Computer Accounting Department of STEKOM University. The study population was 185 students majoring in computer accounting, junior year, STEKOM University. Berdasarkan rumus slovin, maka yang dijadikan sampel sebanyak 126 mahasiswa. all of which were used as research samples. Sources of data in this study were primary and secondary data sources. Data collection techniques using a questionnaires, interviews, and documentation study. Data analysis was carried out descriptively using SPSS 16. The results of this study stated that most students have a perception that using Youtube is good as a media that is only used to watch the material explanation. But, Youtube is not relevant to be used as an application for online interaction. This is because Youtube does not have a feature that allows teachers to interact with students and students with students directly.